Expanding the actions of cortisol and corticosterone in wild vertebrates: A necessary step to overcome the emerging challenges - Vera, Federico (2017)
We conducted a review of scientific articles published between 2000 and 2014 and evaluated how frequently various aspects of cortisol and corticosterone (CORT) actions have been considered in studies on wild vertebrates. Results show that (1) the notion that CORT are stress-responsive hormones is central in our theoretical frameworks and it is reflected by the fact that several articles refer to CORT as “stress hormones”. (2) The large majority of studies do not contemplate the possibility of decrease and no change in CORT levels in response to chronic stressors. (3) Our ideas about CORT actions on energy balance are slanted towards the mobilization of energy, though there are several studies considering -and empirically addressing- CORT's orexigenic actions, particularly in birds. (4) The roles of CORT in mineral-water balance, though widely documented in the biomedical area, are virtually ignored in the literature about wild vertebrates, with the exception of studies in fish. (5) Adrenocorticotropic hormone (ACTH) independent regulation of CORT secretion is also very scarcely considered. (6) The preparative, permissive, suppressive and stimulatory actions of CORT, as described by Sapolsky et al. (2000), are not currently considered by the large majority of authors. We include an extension of the Preparative Hypothesis, proposing that the priming effects of baseline and stress-induced CORT levels increase the threshold of severity necessary for subsequent stimuli to become stressors. Studies on animal ecology and conservation require integration with novel aspects of CORT actions and perspectives developed in other research areas.